Gerakan Sosial Ekofeminisme Melawan Penambangan Marmer di Gunung Mutis Nusa Tenggara Timur - Nagari, Hajeng Pandu (ijd-demos, 2020)
This research aims to understand the movement of ecofeminism that can not be separated from women's unease on the practice of ecological damage. where social movements are the most important factor in realizing social change. Where their presence aims to the realization of better social change and meets the interests of the people. The social movement of ecofeminism discussed in my writing is about the resistance of women from the east who live around the mountain of mutis, who daily perform activities that interact with nature. In 2006 there was a social movement of women in the form of rejection of marble mining around the mountain of mutis done by weaving action in the mining area of Mount Mutis for one year.Tulisan ini bertujuan untuk memahami pergerakan ekofeminisme yang tidak dapat dipisahkan dari ketidaknyamanan perempuan pada praktik kerusakan ekologis. dimana gerakan sosial adalah faktor terpenting dalam mewujudkan perubahan sosial. Dimana kehadiran mereka bertujuan untuk mewujudkan perubahan sosial yang lebih baik dan memenuhi kepentingan rakyat. Gerakan sosial ekofeminisme yang dibahas dalam tulisan saya adalah tentang perlawanan perempuan dari timur yang tinggal di sekitar gunung mutis, yang setiap hari melakukan kegiatan yang berinteraksi dengan alam. Pada 2006 ada gerakan sosial perempuan berupa penolakan penambangan marmer di sekitar gunung mutis yang dilakukan dengan menenun di kawasan penambangan Gunung Mutis selama satu tahun.